Perfil descritivo otimizado, aceitação e parâmetros físico-químicos de vinhos tintos de mesa - Olenka, Ketlyn Lucyani (2015)
The table wine plays a fundamental role in the national wine industry as a source of income for small, medium and large producers. In southwestern Paraná, the city that stands out in the production of red table wines is Salgado Filho. However there are few studies about its features. There are many techniques and thousands of research on red wines, however, the technique of Optimized Descriptive Profile (ODP), because it is a recent methodology is not aware of published works, still used it to describe wines. For the wine industry to promote regional and agro-industrial development, it is necessary to know the possibilities and problems, and on this fact, have been able to establish manufacturing processes based on certain criteria for a safe product and proven quality in the physical, chemical and sensory and that they can win the market. The objective is therefore to apply the optimized descriptive profile, characterize the physical and chemical parameters and verify the acceptance of red wines produced in the municipality of Salgado Filho-PR. Also aimed to verify the adequacy of wines with current legislation and correlate the variables of sensory and instrumental measurements. In developing the methodology we used samples of eight different types of red table wines produced in the municipality of Salgado Filho, all prepared with the varietal Claret. To trace the Optimized Descriptive Profile was used the methodology proposed by Silva (2012). It used the acceptance test and purchase intention to analyze the sensory acceptance. The physical and chemical variables were density, alcohol, volatile acidity, total acidity, reducing sugars and sulfates. Data were analyzed by analysis of variance (ANOVA), Tukey test (p = 5%) and Pearson correlation test. The results show that the ODP, the wines differed as to color, acid taste and body and had no significant differences in aroma, sweet taste and astringency, it can be said that red wines analyzed table feature burgundy color and grape aroma with high intensity notes, with medium intensity for sweet taste and sour taste. light-bodied with low astringency. The acceptance there were no significant differences between the samples and all it obtained high acceptance rate. In general, the physical and chemical parameters fulfilled the Identity and Quality Standards established by Brazilian law. Instrumental and sensory variables showed some positive correlations and strong negative that made it possible to verify the importance of using both measures to reduce demand for time and cost of analysis.